Studi Alterasi, Mineralisasi Dan Inklusi Fluida Prospek Hidrotermal (Pb-Zn-CuÂ±Au-Ag) Kubah Kulonprogo Bagian Selatan, Jawa Tengah - Fadlin, Fadlin; Hajar Sulystiawan, Isnu; Adi Prasetyo, Luthfi (Pusat Survei Geologi, 2019)
Ore potential especially base metals, gold and silver in the Kulonprogo Mountains have been a discussion of Indonesian geologists for a long time, until now its prospects as economic value has not been found, which made it a challenge to conduct an intensive and detailed study. This study is conducted to understand the mineralization-alteration characteristics and the deposit fluid of the study area. The method used in this study is a surface geological mapping, laboratory analysis such as mineragraphy, X-ray diffraction, ore geochemistry (Atomic Absorption Spectrometry-fire assay) and fluid inclusion. Alteration zone of the study area is divided into prophylitic, advanced argilic, argilic and silicification. Vein texture that develop in the study area is a massive quartz, stock work, and vuggy quartz which has NE-SW orientation, while the sulphide mineral abundance which found are enargite, pyrite, chalcopyrite, sphalerite, malachite, and molybdenite, occur in quartz veins or disseminated in gangue rock. Ore geochemistry AAS-fire assay of five vein samples show Au and the highest Ag content shown in sample 3 (Au:3.8. g/t, Ag:10 g/t). Fluid inclusion analysis results show homogenization temperature value (Th) which is 293,4-322,4o C, melting temperature (Tm) is -5,22o C until -6,3o C with average salinity value 10,58-12,89 wt,%NaCl equivalent. Hydrothermal fluid evolution of the study area is at the mixing with cooler phase and less saline fluids. Fluid is estimated from magmatic water that slowly mixed with meteoric water which is shown by the cooling temperature and salinity value. Based on alteration, mineralization, vein texture, ore geochemistry and fluid inclusion data results, therefore the deposit type at the study area is an intermediate epithermal sulphidation (IS).Keyword: alteration-mineralization, intermediate epithermal sulphidation, fluid inclusion, Kulonprogo Dome.